Quantitative Light Fluorescence (QLF) and Polarized White Light (PWL) assessments of dental fluorosis in an epidemiological setting - Pretty I.A. (2014)
Background: To determine if a novel dual camera imaging system employing both polarized white light (PWL) and quantitative light induced fluorescence imaging (QLF) is appropriate for measuring enamel fluorosis in an epidemiological setting. The use of remote and objective scoring systems is of importance in fluorosis assessments due to the potential risk of examiner bias using clinical methods. Methods. Subjects were recruited from a panel previously characterized for fluorosis and caries to ensure a range of fluorosis presentation. A total of 164 children, aged 11years (±1.3) participated following consent. Each child was examined using the novel imaging system, a traditional digital SLR camera, and clinically using the Deans and Thylstrup and Fejerskov (TF) Indices on the upper central and lateral incisors. Polarized white light and SLR images were scored for both Deans and TF indices by raters and fluorescence images were automatically scored using software. Results: Data from 164 children were available with a good distribution of fluorosis severity. The automated software analysis of QLF images demonstrated significant correlations with the clinical examinations for both Deans and TF index. Agreement (measured by weighted Kappas) between examiners scoring clinically, from polarized photographs and from SLR images ranged from 0.56 to 0.92. Conclusions: The study suggests that the use of a digital imaging system to capture images for either automated software analysis, or remote assessment by raters is suitable for epidemiological work. The use of recorded images enables study archiving, assessment by multiple examiners, remote assessment and objectivity due to the blinding of subject status. © 2012 Pretty et al.; licensee BioMed Central Ltd.